2020
DOI: 10.1155/2020/8886914
|View full text |Cite
|
Sign up to set email alerts
|

An Integrative Analysis Reveals the Potential Mechanism between Herbal Medicine Yinchen and Immunoregulation in Hepatocellular Carcinoma

Abstract: Aims. Abundant evidences in traditional Chinese medicine (TCM) supported the therapeutic value of herbal medicine Yinchen in hepatocellular carcinoma (HCC), but the underlying mechanism remains to be investigated. Main Methods. The intersection of immune gene set, module genes, HCC-associated genes, and target genes of Yinchen was employed for further analyses. The module genes were identified by weighted gene coexpression network analysis, and the other three gene sets were obtained from public databases. Sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…Clinical evidence has shown that anti–CTLA-4 therapy can enhance the activation of effector T cells ( Maker et al, 2005 ), increase the ratio of effector T cells to Treg ( Quezada et al, 2006 ; Curran et al, 2010 ; Ou et al, 2018 ), and promote the transport of activated T cells to tumor tissues ( Quezada et al, 2006 ). Our previous study found that traditional Chinese medicine could improve the tumor microenvironment of patients to treat liver cancer and speculated that the immune checkpoints CTLA-4, LAG-3, and BIRC5 are the key targets for activating immune cells to treat liver cancer ( Mo et al, 2020 ). However, only a minority of people can respond to immunotherapy ( Mahoney et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…Clinical evidence has shown that anti–CTLA-4 therapy can enhance the activation of effector T cells ( Maker et al, 2005 ), increase the ratio of effector T cells to Treg ( Quezada et al, 2006 ; Curran et al, 2010 ; Ou et al, 2018 ), and promote the transport of activated T cells to tumor tissues ( Quezada et al, 2006 ). Our previous study found that traditional Chinese medicine could improve the tumor microenvironment of patients to treat liver cancer and speculated that the immune checkpoints CTLA-4, LAG-3, and BIRC5 are the key targets for activating immune cells to treat liver cancer ( Mo et al, 2020 ). However, only a minority of people can respond to immunotherapy ( Mahoney et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…The recently conducted phytochemical analysis of Artemisia annua L. demonstrated the presence of several flavonoids, hydroxycoumarins, and phytosterols, phytochemicals with possible anticancer effects on immune checkpoints [113]. Furthermore, recent gene expression analyses in HCC about Artemisia scoparia demonstrated the increased expression of BIRC5 and secondary expression of CTLA-4 and LAG-3 immune checkpoints and a possible immune activation with this herbal medicine [114]. Further studies evaluating the phytochemical constituent of herbal medications and corresponding effects on the immune checkpoints are needed.…”
Section: Future Perspectivesmentioning
confidence: 99%
“… 5 , 6 Meanwhile, data from both laboratory and clinical studies tend to support the notion that Chinese herbal medicine can ameliorate the and limit HCC progression by improving the pre-tumorigenic microenvironment. 7 , 8 However, the underlying mechanism by which SDS regulates HCC progression remains to be explored.…”
Section: Introductionmentioning
confidence: 99%